(untitled) (Dhaka University Journal of Biological Sciences, 2015)
Bacillus licheniformis MZK05 was subjected to mutation by ultraviolet radiation for enhanced production of keratinase. Of 750 isolates from irradiated plates, 200 colonies that showed zone of casein hydrolysis on Skim Milk Agar were cultured in liquid Feather Meal Medium containing digested feather as carbon and nitrogen source in shake culture at 37ºC. The mutant B. licheniformis MZK05M9 (BlM9) exhibited highest enzyme activity of 170 ± 5.63 U/ml as compared to 74 ± 5.29 U/ml by the wild MZK05. Both the strains were examined for the presence of gene encoded for keratinase (kerA gene) by PCR using primer which showed the product sizes 1156 bp and 520 bp, respectively for MZK05 and BlM9. The keratinase from both strains exhibited a thermal stability of about 97% for 2 hrs at 40°C whereas the keratinase of the mutant strain showed less stability (55%) at 50°C. The BlM9 while cultivated in batch culture in 7 litre bioreactor for production of the keratinase in the Feather Meal Medium, the productivity was found to be double (17,608 U/L/hr) than that of in the shake flask culture (8,525 U/L/hr). This improved strain thus will be very useful for large scale production of keratinase enabling its technical applications in industry. Dhaka Univ. J. Biol. Sci. 24(1): 17-23, 2015 (January)